2019
DOI: 10.3390/polym11091397
|View full text |Cite
|
Sign up to set email alerts
|

Growing Nano-SiO2 on the Surface of Aramid Fibers Assisted by Supercritical CO2 to Enhance the Thermal Stability, Interfacial Shear Strength, and UV Resistance

Abstract: Aramid fibers (AFs) with their high Young′s modulus and tenacity are easy to degrade seriously with ultraviolet (UV) radiation that leads to reduction in their performance, causing premature failure and limiting their outdoor end use. Herein, we report a method to synthesize nano-SiO2 on AFs surfaces in supercritical carbon dioxide (Sc-CO2) to simultaneously improve their UV resistance, thermal stability, and interfacial shear strength (IFSS). The effects of different pressures (10, 12, 14, 16 MPa) on the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…It was found that the SiO 2 nanoparticles were decorated on AF and demonstrated upgrading of structural characteristics and thermic coherence, and the IFSS of the modified AF‐nano‐SiO 2 rises to 64% evaluated with the pristine fibers. Afterward, experiencing ~215 h UV radiation, the UV modified aramid fibers exhibits a lower diminution in elastic modulus, tensile strength, and breaking strain retentive only 72%, 90%, and 86% of the untreated aramid fibers, individually, while those of UV treated and SiO 2 incorporated aramid fibers at 14 MPa hold 91%, 97%, and 95.5% 64 . Ding et al 65 carried out an experiment to coat the SiO 2 nano‐sized particles on the AF skin layer with an optimum concentration of 0.15 mol/L.…”
Section: Grafting Of Nanoparticles Via Scco2mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the SiO 2 nanoparticles were decorated on AF and demonstrated upgrading of structural characteristics and thermic coherence, and the IFSS of the modified AF‐nano‐SiO 2 rises to 64% evaluated with the pristine fibers. Afterward, experiencing ~215 h UV radiation, the UV modified aramid fibers exhibits a lower diminution in elastic modulus, tensile strength, and breaking strain retentive only 72%, 90%, and 86% of the untreated aramid fibers, individually, while those of UV treated and SiO 2 incorporated aramid fibers at 14 MPa hold 91%, 97%, and 95.5% 64 . Ding et al 65 carried out an experiment to coat the SiO 2 nano‐sized particles on the AF skin layer with an optimum concentration of 0.15 mol/L.…”
Section: Grafting Of Nanoparticles Via Scco2mentioning
confidence: 99%
“…Afterward, experiencing $215 h UV radiation, the UV modified aramid fibers exhibits a lower diminution in elastic modulus, tensile strength, and breaking strain retentive only 72%, 90%, and 86% of the untreated aramid fibers, individually, while those of UV treated and SiO 2 incorporated aramid fibers at 14 MPa hold 91%, 97%, and 95.5%. 64 Ding et al 65 Under the effect of forming uneven, intermolecular force, large particles lead to shedding on the surface of the fiber. 66,68 Enhancement of ILSS characteristics essentially relies on these nanoparticles' quantity, orientation, and dispersion.…”
Section: Grafting Of Nanoparticles Via Sccomentioning
confidence: 99%
“…In addition, SiO 2 particle size gradually increases with an increase in time due to the aggregation. 24 At the moment, more flame-retardant molecules adhere to the surface rather than diffusing into cotton fiber. Under the weak physical adsorption, flame-retardant aggregates detach more easily from the fibers, and SiO 2 particles continue to absorb and diffuse into cotton as CO 2 circulates, thereby displaying a decreased trend followed by an increased trend from 90 to 120 min.…”
Section: Effect Of Time On the Flame-retarding Effectmentioning
confidence: 99%
“…Focusing on structural optimization to improve the IFSS of HAFs, a lot of methods referring to the cross-linking of polymer chains and surface modification of aramid fibers have been developed. [35][36][37][38][39][40][41][42][43][44][45] Surface modification usually includes physical and chemical approaches, such as high-energy radiation treatment, [36][37][38] surface coating, [39][40] chemical grafting, [41][42][43][44] and acid-base corrosion. [45] However, these strategies usually have adverse effects on the tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Surface treatment of HAFs by chemical and physical methods, such as chemical grafting, surface coating, plasma irradiation, and so on, can improve surface polarity and roughness to enhance their combination with a matrix. [34,[43][44][45] However, these strategies not only lead to a decrease in tensile strength by destroying the dense structure of fibers, but also require complicated steps. Therefore, it is crucial to develop a simple method to attain both high IFSS and high tensile strength in HAFs.…”
Section: Introductionmentioning
confidence: 99%